The Influence of Social Media on Public Administration - Aris Sarjito (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2023)
Background: The increasing use of social media platforms has profoundly influenced various aspects of society, including public administration. Social media has become a powerful tool in communication, information sharing, and networking, and it can potentially transform how public administration operates. However, several challenges are associated with using social media in this context, such as cyber security risks and the potential for misinformation and fake news. Aim: This research aims to explore the influence of social media on public administration, including how social media platforms are being used in this context, the benefits and challenges associated with social media use, and how public administrators can effectively manage the risks and opportunities related to social media. Qualitative Method and Secondary Data: This research will use qualitative methods to collect and analyze data from secondary sources such as scholarly articles, government reports, and case studies. The data will be analyzed thematically to identify patterns and trends related to the research questions. Findings: The findings of this research suggest that public administrators are using social media platforms for a variety of purposes, including sharing information, receiving feedback, and engaging with citizens. Additionally, using social media has several benefits, such as increased transparency and accountability, greater citizen engagement, and faster communication. However, several challenges are associated with social media use, including cybersecurity risks, privacy concerns, and the potential for misinformation and fake news. Public administrators can effectively manage the risks and opportunities of social media use in their organizations by developing policies and procedures, training staff, and monitoring social media use.